Regular Functions and Cost Register Automata - Alur, Rajeev; D'Antoni, Loris; Deshmukh, Jyotirmoy; Raghothaman, Mukund; Yifei Yuan (2013 28th Annual ACM/IEEE Symposium on Logic in Computer Science, 2013)
We propose a deterministic model for associating costs with strings that is parameterized by operations of interest (such as addition, scaling, and minimum), a notion of regularity that provides a yardstick to measure expressiveness, and study decision problems and theoretical properties of resulting classes of cost functions. Our definition of regularity relies on the theory of string-to-tree transducers, and allows associating costs with events that are conditioned on regular properties of future events. Our model of cost register automata allows computation of regular functions using multiple "write-only" registers whose values can be combined using the allowed set of operations. We show that the classical shortest-path algorithms as well as the algorithms designed for computing discounted costs can be adapted for solving the min-cost problems for the more general classes of functions specified in our model. Cost register automata with the operations of minimum and increment give a deterministic model that is equivalent to weighted automata, an extensively studied nondeterministic model, and this connection results in new insights and new open problems.